Microcontroller-Based Vehicle Parking Automation Design AT89S51 - Benny Agus Simanungkalit (PT Inovasi Pratama Internasional, 2019)
The development of the world of transportation, especially land transportation such as cars as well as the development of shopping centers, restaurants, entertainment and recreation facilities that are growing very rapidly make every entrepreneur who manages parakeet lands to think about parking spaces for future visitors. Customers will feel comfortable and calm if they are easy to find a parking space for their vehicle and easy to find their vehicle again. With this condition, it is necessary to have a tool that can tell customers where the empty parking blocks are so that customers no longer need to circle around just looking for empty parking blocks. The more crowded visitors who come to the parking area, the more busy the parking attendants who manage parking are Manually. Therefore, we need a way to solve this problem. Based on these problems, this research designed a vehicle parking automation based on the AT89S51 microcontroller where the microcontroller will check the condition of the parking entrance, if there is a vehicle in front of the door, the microcontroller will check the conditions in each place. If there is an empty place, the LCD will display the place, then the microcontroller will order to open the parking door. The door will close again after the vehicle enters. This process will continue until all parking spaces are filled.